Analisis Arah Kebijakan Sekolah Terhadap Penggunaan Gawai Android dalam Aktivitas Belajar Peserta Didik di Masa Pandemi Covid-19 - Aswar Aswar; Sulfian Syarif; Sulkipli Sulkipli; Muhammad Amirullah (LPPM Universitas Pendidikan Mandalika, 2021)
This study aims to analyze school policies on the use of smartphones in student learning activities during the Covid-19 pandemic. The research method used a qualitative approach with the type of empirical phenomenology research. The research subjects were obtained through a purposive sampling technique, amounting to 6 people, and this research was conducted online or by phone to teachers, principals, and parents of students. Meanwhile, data analysis used empirical phenomenological analysis techniques The results showed that there were 4 aspects analyzed, namely benefits, drawbacks, learning strategies, and parents' expectations of smartphone-based learning for students. From these four aspects, the school policy directions for the use of smartphones in student learning activities are formulated, including: 1) school policies should provide opportunities for students to use smartphones as a learning tool; 2) school policy should always provide education and oblige weekly meetings between teachers and parents to evaluate the behavior and learning outcomes of students; 3) school policies should facilitate students in the form of learning quotas and provision of wifi so that students and teachers can access the internet properly; 4) school policies should oblige teachers to improve their digital pedagogy competence; 5) school policy should apply the blended learning method during the Covid-19 pandemic.